2018
DOI: 10.1186/s13071-018-3178-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic diversity of Enterocytozoon bieneusi in sheep in China

Abstract: BackgroundEnterocytozoon bieneusi is a common species of microsporidia that not only influences human health but also threatens animal productive performance and value. However, there have been no systematic studies of the prevalence of E. bieneusi in sheep in China.ResultsA total of 953 fecal specimens were collected from sheep from 11 provinces across five regions of China and analyzed for E. bieneusi by nested PCR targeting the ribosomal internal transcribed spacer (ITS). Enterocytozoon bieneusi infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…Similar rate of infection was reported for E. bieneusi in sheep in Northeast China (13.9%, 68/489) (11), Southwest China (10.6%, 70/661) (12), and Egypt (11.2%, 10/89) (13); while lower infection rates were detected in sheep in East-central China (3.4%, 28/832) (14) and Slovakia (0/33) (15). However, a higher prevalence of E. bieneusi was found in Inner Mongolian (China) lambs (77.8%, 126/162) (16), Swedish lambs (68%, 49/72) (17), Brazilian sheep (19.2%, 24/125) (18), and in sheep from some other studies in China (19)(20)(21)(22). The differences in the prevalence are likely due to differences in the geographic and ecological setup.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similar rate of infection was reported for E. bieneusi in sheep in Northeast China (13.9%, 68/489) (11), Southwest China (10.6%, 70/661) (12), and Egypt (11.2%, 10/89) (13); while lower infection rates were detected in sheep in East-central China (3.4%, 28/832) (14) and Slovakia (0/33) (15). However, a higher prevalence of E. bieneusi was found in Inner Mongolian (China) lambs (77.8%, 126/162) (16), Swedish lambs (68%, 49/72) (17), Brazilian sheep (19.2%, 24/125) (18), and in sheep from some other studies in China (19)(20)(21)(22). The differences in the prevalence are likely due to differences in the geographic and ecological setup.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies showed the variation in infection rates of E. bieneusi in different age group of sheep, as well as in lambs (12,14,17,21). In present study, only lambs younger than 3 months were assessed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, 11 E. bieneui genotypes were identified, including six known genotypes (D, I, BEB6, CHG3, CHG5, and CHG2) and five novel genotypes (HNE-I to HNE-V). Of these, genotype D, I, and BEB6 have been found in humans, and genotypes CHG2, CHG3, and CHG5 were commonly found in goats and sheep in China (Shi et al, 2016; Chen et al, 2018; Yang et al, 2018; Li et al, 2019a). Out of the 11 genotypes identified in the present study, genotype D is the most frequently detected in humans, and has been found in both HIV-positive patients and HIV-negative individuals from America, Europe, Asia, and Africa (Matos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Microsporidia are small, spore forming, obligate intracellular protozoa detected in many hosts. Up till now, 1300 microsporidian species or more, related to 150 genera, were detected [1] . Ent.…”
Section: Introductionmentioning
confidence: 99%